Characterization of Pisolithus orientalis in culture and in vitro mycorrhization with Eucalyptus camaldulensis and Pinus kesiya - J. Kumla (2018)
© Guizhou Academy of Agricultural Sciences. A basidiome of Pisolithus orientalis was collected from northern Thailand and a pure culture was isolated. This study aimed to investigate the suitable mycelial growth conditions of this fungus and its ability to form ectomycorrhizal symbiosis with seedlings of Eucalyptus camaldulensis and Pinus kesiya in vitro. The fungal mycelium grew well on Murashige and Skoog medium that was adjusted to pH 5.0 at 30 °C. The plant seedlings were inoculated with fungal mycelium. The mycorrhization was first observed on pine and eucalyptus at 10 and 12 weeks after inoculation, respectively. Moreover, the identification of mycorrhizal association was confirmed by molecular methods. This is the first report of pure culture synthesis of Pis. orientalis mycorrhizae and the compatible of mycorrhizal formation of E. camaldulensis.